2009
DOI: 10.1038/leu.2009.225
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 germline genetic variation affects disease susceptibility in primary myelofibrosis regardless of V617F mutational status: nullizygosity for the JAK2 46/1 haplotype is associated with inferior survival

Abstract: A common JAK2 germline haplotype (46/1) has been associated with JAK2V617F (VF)-positive myeloproliferative neoplasms. The rs12343867 SNP (C/T) tags this haplotype. A total of 130 patients (77 VF-positive) with primary myelofibrosis (PMF) were analyzed for this informative SNP, using bone marrow-derived DNA. The observed 46/1 C allele frequencies in VF-positive (50%) and VFnegative (36%) patients were both significantly higher than expected in population controls (Po0.01). Genotype distributions in VF-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
92
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 39 publications
11
92
4
Order By: Relevance
“…[2][3][4][5] We confirmed these observations in two recent papers 6,7 and also showed increased JAK2 46/1 haplotype frequency in VF-negative essential thrombocythemia (ET) 6 and primary myelofibrosis (PMF). 7 In the latter two studies, the JAK2 46/1 haplotype frequencies in both PMF (44%) and ET (41%) were significantly higher than that of the Wellcome Trust Case Control Consortium (WTCCC) (24%) or local (28%) control population, but similar in VF-positive versus VF-negative PMF (37 versus 36%) or ET (41 versus 38%), after adjusting for VF allele burden (that is, considering only patients with low allele burden to minimize allelic distortion from acquired uniparental disomy). A functional variant associated with the JAK2 46/1 haplotype could promote altered signaling and influence phenotype in the presence of VF or other JAK-STAT-relevant mutation, such as mutant MPL.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…[2][3][4][5] We confirmed these observations in two recent papers 6,7 and also showed increased JAK2 46/1 haplotype frequency in VF-negative essential thrombocythemia (ET) 6 and primary myelofibrosis (PMF). 7 In the latter two studies, the JAK2 46/1 haplotype frequencies in both PMF (44%) and ET (41%) were significantly higher than that of the Wellcome Trust Case Control Consortium (WTCCC) (24%) or local (28%) control population, but similar in VF-positive versus VF-negative PMF (37 versus 36%) or ET (41 versus 38%), after adjusting for VF allele burden (that is, considering only patients with low allele burden to minimize allelic distortion from acquired uniparental disomy). A functional variant associated with the JAK2 46/1 haplotype could promote altered signaling and influence phenotype in the presence of VF or other JAK-STAT-relevant mutation, such as mutant MPL.…”
supporting
confidence: 76%
“…6 It could be demonstrated that the AML1-ETO fusion gene and FLT3 length mutations collaborate in inducing acute leukemia in mice and there is first evidence that the combination of AML1-ETO and JAK2 V617F mutations results in AML. 7,8 Recently, several studies have shown that in core-binding factor AML up to 40% of t(8;21) patients have additional mutations of the KIT gene, while the total incidence of c-KIT mutations in all AML is B5%. 9,10 Mutations of the NRAS gene have been reported in up to 10% of AML1-ETO cases, whereas other mutations in genes as AML1 and PU.1 occur only rarely in combination with t(8;21).…”
mentioning
confidence: 99%
“…MPL and JAK2 mutation analyses were performed according to previously published methods. [26][27][28][29] IDH1 and IDH2 mutations were analyzed by direct sequencing and/or high-resolution melting assay. 30 Unfavorable karyotype designation 31 and International Prognostic Scoring System (IPSS), 32 DIPSS, 33 and DIPSSplus 21 21 Leukemic transformation risk was considered high in the presence of unfavorable karyotype or platelet count less than 100 ϫ 10 9 /L or low in the absence of both of these risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a number of DIPSS-plus-independent risk factors in PMF were identified and they include driver mutations other than type 1 or type 1-like CALR variants [44], monosomal karyotype [74], nullizygosity for JAK2 46/1 haplotype [75], low JAK2V617F allele burden [76,77], presence or number [78] of IDH1/2 [51], EZH2 [51], SRSF2 [51], or ASXL1 mutations [51], and increased serum IL-8 [79], IL-2R [79] or serum free light chain levels [80]. In a recent international study of 570 patients with PMF [81], the authors reported the longest …”
Section: Advances In Prognosticationmentioning
confidence: 99%